Pendampingan Pembelajaran Bahasa Arab Melalui Media Lagu di SDIT Al Ghazali - Anda Yani, Duwi; Rahmah,, Yulia; Delima, Delima (UNIVERSITAS SERAMBI MEKKAH, 2025)
Arabic language learning at SDIT Al Ghazali faces challenges in attracting students' interest due to monotonous teaching methods. This article discusses an Arabic language learning assistance program through song media, which focuses on increasing students' motivation, understanding and Arabic language skills. The Participatory Action Research (PAR) method is applied in three stages: preparation, implementation, and evaluation. The results show that the use of song media is able to create an interactive learning atmosphere, increase student enthusiasm, and show a significant increase in Arabic language skills. In conclusion, the use of song media in learning Arabic at SDIT Al Ghazali has proven to be effective and needs to be continued for further development.